Irrigated plots: reversing degradation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In the majority of irrigated areas in sub-Saharan Africa, poor management of the irrigation inefficient drainage, and paddy rice grown on soil which is too sandy have led to a rapid rise in groundwater levels, increasing aluminium toxicity and...